RESENHAS - César, Constança Marcondes (Reflexão, 2024)
RICOEUR, Paul, Temps et Récit, vol. I. Paris, Seuil, 1983 RICOEUR, Paul, Temps et Récit, vol. II. Paris, Seuil, 1984. FERREIRA DA SILVA, Dora ( org, ) A Poesia Mística de San Juan de la Cruz. São Paulo, Cultrix, 1985.